Perancangan Buku Ilustrasi Permainan Tradisonal sebagai Upaya Melestarikan Budaya Lokal - Feri Irawan; Jupriani Jupriani (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Traditional games are an important part of cultural heritage rich in educational, social, and moral values. However, technological developments in the modern era have led children in Merangin Regency to abandon traditional games. They spend more time with gadgets, causing a decline in social interaction and awareness of local culture. Among various types of traditional games, congklak has become one of the least played. This situation encouraged designers to create an educational and engaging medium for children. As a solution, an Illustrated Book of the Traditional Game Congklak of Merangin Regency was designed as both a learning medium and an effort to preserve local culture. The illustrated book was chosen because it can convey messages visually and verbally in an appealing way, making it easier for readers to understand the story and the values contained within it. The design process used the 4D method (Define, Design, Develop, Disseminate) with 5W+1H analysis to meet design needs. In addition to the main book, supporting media such as posters, x-banners, t-shirts, tumblers, tote bags, bookmarks, and e-books were also developed. The design feasibility test obtained a score of 90%, categorized as very feasible, covering aspects of storyline, illustration, layout, and language. The content feasibility test achieved a score of 100%, also categorized as very feasible, including cultural, cognitive, social, and character education values. This book is declared highly feasible and effective as a learning medium as well as a means of preserving the local culture of Merangin Regency.